2023
DOI: 10.1039/d2lc00636g
|View full text |Cite
|
Sign up to set email alerts
|

Image-based cell sorting using focused travelling surface acoustic waves

Abstract: Real-time morpho-rheological analysis of cells by RT-DC, combined with the improved sorting performance of an on chip FTSAW-based microactuator enables efficient label-free image-based sorting of various cell types with distinct physical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…Once a vast number of mechanics datasets connected to omics profiles is available, it will be straightforward to develop a next generation artificial intelligence algorithm predicting cell stiffness from given omics profiles. Apart from analyzing divergent cell states, the search for mechanical regulators could be complemented by looking into omics data of cells from unimodal populations sorted by their mechanical properties — a pursuit that with the advent of high-throughput methods for mechanics-based sorting of cells, such as sorting RT-DC (88, 89) or passive filtration-based approaches (85), becomes a realistic objective.…”
Section: Discussionmentioning
confidence: 99%
“…Once a vast number of mechanics datasets connected to omics profiles is available, it will be straightforward to develop a next generation artificial intelligence algorithm predicting cell stiffness from given omics profiles. Apart from analyzing divergent cell states, the search for mechanical regulators could be complemented by looking into omics data of cells from unimodal populations sorted by their mechanical properties — a pursuit that with the advent of high-throughput methods for mechanics-based sorting of cells, such as sorting RT-DC (88, 89) or passive filtration-based approaches (85), becomes a realistic objective.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of high-quality images to identify morphological differences between groups of cells and to use them for cell sorting applications is evident in recent works where the high capabilities of artificial intelligence using convolutional neuronal network (CNN) approaches help to classify and even sort blood cells based on label-free bright field images. 42–44 These results highlight the major importance of having high-quality images of the cells to detect unexpected morphological patterns that only an algorithm can identify after processing thousands of cells. We believe that high-quality microscopy (bright field in the combination with fluorescence) is fundamental for linking physiological properties of a cell to its morphology.…”
Section: Discussionmentioning
confidence: 96%
“…Firstly, the acoustic radiation force acting on the particles mainly depends on the material properties (e.g., density and compressibility) and size (diameter) of the particles. Recently, Nawaz et al 165 have shown that they are the first to use TSAWs to sort small cells such as platelets, but with a purity of only 40%, mainly because the small acoustic radiation force acting on platelets cannot push them to deflect sufficiently. In this respect, improvements can be made by adjusting IDTs parameters such as increasing frequency and decreasing aperture.…”
Section: Discussionmentioning
confidence: 99%